The Suitability of the Remedy of Specific Performance to Breach of A "Player’s Contract" with Specific Reference to the Mapoe and Santos Cases - Mould, Kenneth (Potchefstroom Electronic Law Journal, 2017)
During the 1990s, rugby union formation in the Republic of South Africa developed rapidly from a system of strict amateurism to one of professionalism. Professional participants in the sport received salaries for participation, and rugby became a business like any other. As in all forms of business, rugby had to be regulated more efficiently than had previously been the case. Tighter regulations were instituted by governing bodies, and ultimately labour legislation became applicable to professional rugby. A professional sportsman or woman participating in a team sport is generally considered an employee. This means that the same principles that govern employees in general should also apply to professional sportsmen and women. The exact nature of the "player’s contract", a term generally used to describe the contract of employment between a professional sportsman or sportswoman and his or her employer, deserves closer attention. It has been argued with much merit that the "player’s contract", while in essence a contract of employment, possesses certain sui generis characteristics. The first aim of this article is to demonstrate how this statement is in fact a substantial one. If it is concluded that the "player’s contract" is in fact a sui generis contract of employment, the most suitable remedy in case of breach of contract must be determined. The second aim of this article is to indicate why the remedy of specific performance, which is generally not granted in cases where the defaulting party has to provide services of a personal nature, is the most suitable remedy in case of breach of "player’s contracts". To substantiate this statement, recent applicable case law is investigated and discussed, particularly the recent case of Vrystaat Cheetahs (Edms) Beperk v Mapoe. Suggestions are finally offered as to how breach of "player’s contracts" should be approached by South African courts in future.